1985
DOI: 10.1038/313318a0
|View full text |Cite
|
Sign up to set email alerts
|

Early steps of lymphocyte activation bypassed by synergy between calcium ionophores and phorbol ester

Abstract: Although it has been proposed that the activation of T lymphocytes is mediated by an early rise in cytosolic calcium concentration, it has not been possible to mimic antigen- or mitogen-induced mouse lymphocyte activation by calcium ionophores that bypass receptor-mediated processes. There is now evidence from other systems that the rise in cytosolic calcium which follows receptor triggering is preceded by the breakdown of phosphatidylinositol bisphosphate into 1,2-diacylglycerol and inositol trisphosphate. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
290
0
1

Year Published

1988
1988
2010
2010

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 698 publications
(301 citation statements)
references
References 18 publications
10
290
0
1
Order By: Relevance
“…Activated T cells of NOD origin were reported to express higher levels of ICOS (32). Although Ctex constitutes the major locus involved in the control of CTLA-4 expression, we observed that this locus does not influences ICOS protein expression in NOD mice (Supplemental Fig.…”
Section: Nod Allele Of Thementioning
confidence: 59%
See 1 more Smart Citation
“…Activated T cells of NOD origin were reported to express higher levels of ICOS (32). Although Ctex constitutes the major locus involved in the control of CTLA-4 expression, we observed that this locus does not influences ICOS protein expression in NOD mice (Supplemental Fig.…”
Section: Nod Allele Of Thementioning
confidence: 59%
“…5D, 5E). As shown in The phorbol ester PMA and the calcium ionophore ionomycin fully trigger activation of T cells, bypassing the cross-linking of the TCR/CD3 complex (32). Therefore, we reasoned that the addition of PMA plus ionomycin should improve the impaired T cell activation observed in NOD T cells if it was conferred by the NOD allele of Cd3z.…”
Section: Nod Allele Of Thementioning
confidence: 99%
“…DAG stimulates protein kinase C whereas IP3 mediates elevation of cellular Ca2+ concentrations [3]. Cascades of biochemical processes consequent to these early events eventually synergize in securing commitment of the lymphocyte to mitosis [4].…”
Section: Introductionmentioning
confidence: 99%
“…52 and 53), and ionomycin, a calcium ionophore that activates downstream calcium-dependent signaling pathways (54). Combinations of PMA and ionomycin have long been used to initiate activation signals in lymphocytes (55,56).…”
Section: Suppression Of Rag Responses and L Chain Rearrangements By Pmentioning
confidence: 99%